EFISIENSI SISTEM PEMASARAN CENGKEH (Syzygium aromaticum) DI KABUPATEN PESISIR BARAT - Siti Meiska Amelia; Ali Ibrahim Hasyim; Suriaty Situmorang (Lampung University, 2019)
This research aimed to analyze the efficiency of clove marketing system in Pesisir Barat Regency. The research data was collected in Karya Penggawa and Pesisir Utara Subdistrict of Pesisir Barat Regency in January – February 2017. This location was chosen purposively. Farmer respondents were chosen randomly, while marketing channel respondents were taken by tracing marketing networks. Data consisted of primary and secondary data. Data analysis included analysis of marketing system efficiency. The results showed that the marketing system of clove in Pesisir Barat Regency was inefficient with producer share (PS) 96.51%, with the following conditions as followed. The market structure was in imperfect competition (oligopsoni), clove farmers had no difficulty in marketing their product and there was one marketing channel in the market performance. Marketing margin was Rp3.157,46/kg and Ratio Profit Margin (RPM) 0.93%.Key words: clove, efficiency, marketing system